2014
DOI: 10.1016/j.cell.2014.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The Noncoding RNA Revolution—Trashing Old Rules to Forge New Ones

Abstract: Noncoding RNAs (ncRNAs) accomplish a remarkable variety of biological functions. They regulate gene expression at the levels of transcription, RNA processing, and translation. They protect genomes from foreign nucleic acids. They can guide DNA synthesis or genome rearrangement. For ribozymes and riboswitches, the RNA structure itself provides the biological function, but most ncRNAs operate as RNA-protein complexes, including ribosomes, snRNPs, snoRNPs, telomerase, microRNAs, and long ncRNAs. Many, though not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
1,592
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,079 publications
(1,602 citation statements)
references
References 209 publications
5
1,592
0
5
Order By: Relevance
“…More recently, we have come to learn that here too small RNA's (such as CRISPRS or even tRNAs) are much more involved in basic regulatory functions (Nicolas et al 2013. And in eukaryotes, there has been a big change in our thinking regarding regulation by RNA (Cech and Steitz 2014). Thus, we propose to place RNA-based regulation in a more fundamental role (Supplementary File 3).…”
Section: The Basic Motif: Virus-derived Addiction Modules Promote Gromentioning
confidence: 99%
“…More recently, we have come to learn that here too small RNA's (such as CRISPRS or even tRNAs) are much more involved in basic regulatory functions (Nicolas et al 2013. And in eukaryotes, there has been a big change in our thinking regarding regulation by RNA (Cech and Steitz 2014). Thus, we propose to place RNA-based regulation in a more fundamental role (Supplementary File 3).…”
Section: The Basic Motif: Virus-derived Addiction Modules Promote Gromentioning
confidence: 99%
“…The lncRNAs work in a complicated way as critical regulator of epigenetic modulation, transcription and translation in a spatiotemporal manner 13, 14. SNHG14, alternatively named UBE3A‐ATS, is located on chromosome 15q11.2.…”
Section: Introductionmentioning
confidence: 99%
“…long noncoding RNAs (lncRNAs) are the new member of ncRNA with a length >200 nt, and lacking of protein‐coding capacity 9. To date, increasing evidence have demonstrated that lncRNAs are widely expressed in most of organ tissues, and participate in various cellular biological process, including X chromatin imprinting, muscle cells differentiation, immune response, cell fate decision, tumor cell proliferation, and drug resistance 10, 11. Importantly, RNA sequencing and microarray analyses of tumor and normal tissues in diverse types of human cancers revealed that thousands of lncRNAs are dysregulated in cancer tissues, and part of these lncRNAs are emerging as key molecules during carcinogenesis 12, 13.…”
Section: Introductionmentioning
confidence: 99%